2007
DOI: 10.1103/physreve.76.031404
|View full text |Cite
|
Sign up to set email alerts
|

Bond formation and slow heterogeneous dynamics in adhesive spheres with long-ranged repulsion: Quantitative test of mode coupling theory

Abstract: A colloidal system of spheres interacting with both a deep and narrow attractive potential and a shallow long-ranged barrier exhibits a prepeak in the static structure factor. This peak can be related to an additional mesoscopic length scale of clusters and/or voids in the system. Simulation studies of this system have revealed that it vitrifies upon increasing the attraction into a gel-like solid at intermediate densities. The dynamics at the mesoscopic length scale corresponding to the prepeak represents the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…However, Henrich and coworkers have shown by the self-consistent MCT calculation that the presence of the prepeak does not affect the nature of the glass transition, that is, the slow structural relaxation at the prepeak scarcely affects the microscopic dynamics. 36 Their result is consistent with that of ionic liquid in Ref. 34 in that the slow structural relaxation at the prepeak does not appear in the memory function of the intermediate scattering function at the main peak.…”
Section: Fig 7 the Cross-correlation Function Between The Two-body supporting
confidence: 85%
See 1 more Smart Citation
“…However, Henrich and coworkers have shown by the self-consistent MCT calculation that the presence of the prepeak does not affect the nature of the glass transition, that is, the slow structural relaxation at the prepeak scarcely affects the microscopic dynamics. 36 Their result is consistent with that of ionic liquid in Ref. 34 in that the slow structural relaxation at the prepeak does not appear in the memory function of the intermediate scattering function at the main peak.…”
Section: Fig 7 the Cross-correlation Function Between The Two-body supporting
confidence: 85%
“…The glass transition of these colloidal systems was investigated in detail both by computer simulations and the self-consistent MCT calculations. 35,36 The long-range repulsive interaction leads to the formation of the mesoscopic structure represented as the prepeak, and the structural relaxation at the prepeak is the slowest microscopic dynamics. However, Henrich and coworkers have shown by the self-consistent MCT calculation that the presence of the prepeak does not affect the nature of the glass transition, that is, the slow structural relaxation at the prepeak scarcely affects the microscopic dynamics.…”
Section: Fig 7 the Cross-correlation Function Between The Two-body mentioning
confidence: 99%
“…Yet, for small q, the situation is more intricate. Let us also note that for systems whose glass transition features are dominated by the large-q behavior of the static structure factor, the destructive interference induced by pre-averaging the MCT input can lead to severe changes in the qualitative dynamics [21]. This particularly concerns polydisperse colloid-polymer systems with short-ranged (depletion-induced) interaction among the colloids.…”
Section: Data Analysis a Structure Factorsmentioning
confidence: 99%
“…Thus, testing the "full MCT", that is, putting to test the dynamics as calculated within the theory from the static structure factor (without invoking asymptotic or schematic limits of the theory's equations) against the measured one, is a task for molecular dynamics simulations, and has been performed on the standard glassforming binary Lennard-Jones mixture [14,[16][17][18], on hard-sphere mixtures [19,20], soft spheres with shortranged attraction [21,22], and in more complicated systems such as network-forming strong liquids [23,24], metallic glasses [25], polymer melts [26], or computer models of organic glass formers such as ortho-terphenyl [27,28]. As it turns out, these systems are already quite demanding for MCT, although the theory fares well in a qualitative description of the dynamical phenomena, sometimes even quantiatively (most notably, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its simplicity, the model system exhibits interesting microphases owing to a competition of the short-ranged attraction and longer-ranged repulsion. [11][12][13][14][15] The interparticle potential is represented by a double-Yukawa ͑DY͒ function. It has been previously demonstrated that the properties of the Yukawa system can be accurately represented by a density functional theory ͑DFT͒ that incorporates the fundamental measure theory ͑FMT͒ for the excluded volume effects and the direct correlation functions for both attractive and repulsive components of the DY interparticle potential.…”
Section: Introductionmentioning
confidence: 99%